Cloning of a Transglutaminase Gene from Streptomyces thioluteus TTA 02 SDS 14 - Seprianto Seprianto; Dewi Seswita Zilda; Yusro Nuri Fawzya; Suharsono Suharsono; Puspita Lisdiyanti; Agustinus Robert Uria (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2016)
Microbial Transglutaminase (MTGase, EC 2.3.2.13) is an enzyme that catalyzes the transfer of acyl group. Many microbial strains that produce MTGase belong to Streptomyces members. This research was aimed at cloning of a MTGase gene. PCR–based screening of ten MTGase-producing streptomyces isolates from soil in West Nusa Tenggara led to detection of one potential isolate, designated as TTA 02 SDS 14. The partial MTGase-encoding gene (470 bp) was amplified by PCR and sequenced. The sequence result indicate its similarity of 93 % with that of Streptomyces cinnamoneus. The 16S rRNA gene analysis showed its identity as Streptomyces thioleteus. Fosmid-based construction of a genomic library from the isolate and subsequent screening led to the isolation of a 40-Kb fosmid harboring a MTGase gene.